Cancer drugs: Highlighting the molecular mechanisms of cardiotoxicity - Tabane, Keo; Vorobiof, Daniel A. (SA Heart Journal, 2017)
The treatment options for patients with cancer have increased rapidly in the last decade with the introduction of newer chemotherapy drugs, targeted agents and monoclonal antibodies. Most of these drugs are aimed at interrupting proliferative signalling, with consequent apoptosis of cancer cells. Because most of the new drugs are multi-targeted, there is a likelihood of so called “off target” effects, where other kinases which are not the primary targets of the drug, are also inhibited. This has led to unforeseen toxicities and, in this commentary, we will focus on the molecular mechanisms underlying cardiotoxicities as a result of cancer therapies. However, cardiotoxicity is not a new concern as the older generation chemotherapies, like anthracyclines, are known to commonly cause irreversible cardiomyopathy, mostly as a result of induced DNA damage and oxidative stress. Over the years, clinicians have adopted some methods of diminishing the incidence of this side-effect and therefore improving patient safety. Trying to decipher the complicated pathways underlying cardiotoxicity helps the scientifi c community to design new drugs that are tumoricidal, whilst sparing normal tissue and as such limiting unwanted side-effects. This has become ever so important, as oncologists cure more patients of cancer, and some previously incurable cancers are increasingly being converted into chronic illnesses. A relationship between the cardiologist and the oncologist has become mandatory to ensure close monitoring of such patients and offering appropriate management, should cardiotoxicities arise.